(untitled) (Applied Biological Research, 2023)
The present study was aimed to evaluate the effect of different biocontrol agents, botanicals and fungicides on crop yield and stem gall disease of coriander (Coriandrum sativum L.), caused by Protomyces macrosporus Unger. The effectiveness of plant leaf extracts, fungicides and bioagents were evaluated against the test fungus under in vitro conditions by using poisoned food technique and further evaluated under field conditions for disease managemenand crop yield improvement. Among the biocontrol agents and botanicals evaluated, Pseudomonas fluorescens and datura leaf extract were most effective in in inhibiting the pathogenic growth; whereas amongst fungicides, metalaxyl + mancozeb @ 0.2% and copper oxychloride @ 0.2% were significantly superior with 100% pathogenic growth inhibition under in vitro conditions. Under field conditions, seed treatment and foliar spray of metalaxyl + mancozeb and copper oxychloride @ 0.2% proved most effective in managing the disease as well as improved crop yield (1493.06 and 1284.72 kg ha-1, respectively) in comparison to the control (729.17 kg ha-1).